Symbols and Images of Peace in the Meranaw Epic Darangen - Casan, Hammim B. (Future Science / FSH-PH Publications, 2024)
A profound relationship exists between literature and peace that transcends centuries and cultures. In the southern Philippines, the Meranaw people consider peace to be more than a mere notion; it is an intrinsic aspect of their cultural and traditional way of life. Furthermore, by applying critical discourse analysis to the symbols and images in the Volume 1 of the Meranaw epic Darangen, this literary research elucidates the significance of peace. This is further supported by Aristotle's Theory of Poetry, Stuart Hall's Cultural Studies, Sigmund Freud's Psychoanalytic Theory, and Karl Marx's Marxism. Moreover, it is found that fear, marriage, dialogue, status, royalty, tolerance, power, nobility and proletariat, cleanliness, communication, discontinuity, death, politeness, sacrifice, pride, royalty, divinity, harmony, support, safety, divine protection, and courage are the meanings of the symbols and images in relation to peace. Each symbol and image in the epic illustrate how the Meranaw people define peace. Peace is represented in marriage, gatherings in the torogan, the colors of the malong, flags, jewelry and gold, gifts, and divine like the spirits, magic chair, and shield in the epic. Further, the epic portrays that peace for the Meranaw people can only be achieved by valuing their honor, dignity, self-esteem, and reputation. Hence, this study revealed the symbols and images in the epic that reflect the concepts of peace in the Meranaw community.